Do alien species affect native freshwater megafauna? - Chen, Xing; Jähnig, Sonja C.; Jeschke, Jonathan M.; Evans, Thomas G.; He, Fengzhi (Freshwater biology, 2023)
1. Freshwater megafauna species (i.e., animals that can reach a body mass ≥30 kg, including fish, reptiles, mammals, and amphibians) play important roles in freshwater systems (e.g., by influencing habitat structure, trophic dynamics, or the dispersal of smaller species). As they tend to be large and charismatic, they may also function as flagship umbrella species in future freshwater conservation initiatives. Despite this, as a group they are highly threatened, and our knowledge of the nature of these threats is limited. In this study, we aim to improve our understanding of the impacts of alien species on native freshwater megafauna. 2. We undertook the first global assessment of the impacts of alien species on native freshwater megafauna using the Environmental Impact Classification for Alien Taxa (EICAT) framework. We conducted a literature review to identify published and grey literature on impacts, which we quantified and categorised by their severity and type, following the EICAT guidelines. 3. Negative impacts on native freshwater megafauna were caused by 61 alien species from a diverse range of taxonomic groups, including both freshwater and terrestrial alien species, and both vertebrates and invertebrates. They adversely affected 44 of 216 native freshwater megafauna species, including amphibians, fish, mammals, and reptiles. The Great Lakes Basin had the highest number of affected megafauna species (six of the 14 freshwater megafauna species it supports, mainly fish). Impacts occurred through a broad range of mechanisms (10 of the 12 identified mechanisms under EICAT); predation and competition were the most frequently reported mechanisms. Some impacts were relatively minor, adversely affecting the performance of individuals of native freshwater megafauna species. However, some reported impacts did cause declining populations of native freshwater megafauna species, and one impact contributed to the local extinction of the ship sturgeon (Acipenser nudiventris) in the Aral Sea. The vulnerability of native freshwater megafauna species to different types of impact varies during different life‐cycle stages (egg, juvenile, and adult). 4. Our understanding of impacts posed by alien species on native freshwater megafauna is limited because data are unavailable for many regions, particularly the Global South, including hotspots for freshwater megafauna diversity such as the Amazon, Congo, Mekong, and Ganges‐Brahmaputra basins. Freshwater megafauna species are often subject to multiple threats, which makes it difficult to determine the significance of alien species impacts relative to other threats such as habitat degradation and overexploitation. In addition, short‐term studies are likely to be masking the severity of the impacts identified. We call for more long‐term studies that attempt to identify population‐level impacts, and for studies that identify impacts in data‐deficient regions. 5. The EICAT assessments undertaken for this study will be reviewed by the EICAT Authority and subsequently incorporated into the IUCN EICAT database. They may be used to guide future research and conservation actions.